Legitimacy as a Precondition for the Recognition of New Governments: A Case of Libya - Hamed Hasyemi Saugheh; Rohaida Nordin (Faculty of Law, Sriwijaya University, Indonesia, 2018)
Recognition of new Stets and governments is a political act with legal reverberations. Although the recognition of new States and governments is a traditional concept of international law but the challenging recognition of the transitional government of Libya proved that this traditional concept still can be highly exigent. Traditionally, the States in providing recognition to a new government follow their own benefits and privileges and rarely consider the structure, capacity and public support for the new government. If the rule of law and respecting democracy is going to be means of promoting peace and security is various areas of the world, is not it time to redefine the traditional concepts of international law (included of recognition of new States and government) from a new perspective? Considering the fact that, the existence of a legitimate authority in a group enhances the effective functioning of that group and reduces the internal conflicts, it seems that it is time to expand the political concept of legitimacy of the authorities into the international law. Is there any State practice to support the argument? In this article, the existence of norm creating forces and role of legitimacy in the recognition of the Libyan Transitional Government is going to be analysed. The After studying the role of legitimacy of the Libyan NTC in passing the sovereignty from the past regime to the new government by the international community, the effect of lack of legitimacy on the previous regime will be examined and the question of withdrawing of recognition of governments will be addressed.